Keefektifan Media Audiovisual Terhadap Motivasi Belajar Siswa di Sekolah Dasar - Huda, Muhammad Jamalul; Pertiwi, Anisa Yuni (Jurnal Pendidikan : Riset dan Konseptual, 2018)
The absence of media in the learning process has an impact on students' learning motivation which is still low. This study aims to determine the effectiveness of audiovisual media on the motivation to learn Indonesian. This type of research is an experiment with a population of 44 students. The sample in the study was taken with saturated sampling technique. Data collection techniques through interviews, documentation, and questionnaires. Hypothesis test results of differences in learning motivation using Independent Samples T Test shows the value of t count> t table (3.142> 2.018) and a significance value of 0.003 <0.05, while the results of the effectiveness hypothesis testing using the party t test shows the value of t count> t table (2.173> 2.080) and significance value 0.041 <0.05.